Accounting Valuations in Nationalization Settlements - Mccosker, Joseph S. (Journal of International Business Studies, 1973)
Many of the less-developed countries have required foreign companies to settle nationalization claims on a basis of book values. These book values are based on generally accepted accounting principles that tend to make book values lower than current fair values. As a result, nationalization claims that are settled on the basis of book values are biased against the owners of the nationalized companies. Accountants should disclose, in notes to the financial statements and in the auditors' reports, that book values do not reflect current fair values, so that it will be evident that the financial statements do not provide an appropriate basis for settling nationalization claims.